Physiotherapeutic interventions in the treatment of Autism Spectrum Disorder: An integrative review (Research, Society and Development, 2024)
Introduction: Autism spectrum disorder (ASD) is a neurological disorder, characterized by difficulty in communication and social interaction, stereotypical behaviors, as well as motor and sensory restrictions, which cause important impacts on the daily lives of children diagnosed with ASD. Objective: This study aimed to address the main treatments for ASD exposed in the literature and add information about this so that physiotherapists, on an individual basis, can develop the appropriate treatment plan for each child. Methodology: It consists of a non-systematic integrative bibliographic review, regarding physiotherapeutic interventions in the treatment of ASD. In this review, articles were selected between the years 2019 and 2024, in the electronic databases PUBMED, SCIELO and PEDro, in Portuguese, Spanish and English. Results: A total of 7 articles were selected covering the physiotherapeutic resources used in the treatment of Autism, such as hydrotherapy, hippotherapy, aerobic activity, postural and multimodal sensorimotor training. All studies showed significant improvements in cognition, postural stability, gait and sensitivity, offering a better quality of life for the child. Conclusion: Through this study, it was possible to demonstrate the importance of physiotherapists in treating children with ASD, due to the wide variety of resources they can use.